Mixture of auxinic herbicides for the control of Conyza spp. and its phytotoxic effects on soybean sown in sequence - Pessoni Pereira Nascimento Borges, Rafael; Silva, Paulo Vinicius da; Silva de Medeiros, Elias; Ferrari Schedenffeldt, Bruna [UNESP]; Facco Celin, Elaine; Pauluzi Shingu, Caio Haruo; Maraus Marostica, Lucas; Soares França, Nayane; Lemos Cervo, Luiz Pedro; Mauad, Munir; Vougodo Salmazo, Pedro Antônio; Monquero, Patricia Andrea (Taylor & Francis, 2025)
The combination of auxin-mimicking herbicides from different chemical groups offers an alternative for controlling fleabane (Conyza spp.) in soybean pre-sowing, but care is needed to avoid phytotoxicity. This study evaluated the effectiveness of auxinic herbicide mixtures in controlling Conyza spp. and their residual effects on soybean plants. A randomized block field experiment tested 13 combinations of auxinic herbicides with glyphosate, followed by glufosinate 14 days after application (DAA). At 42 DAA, all the treatments provided satisfactory control, with triclopyr + halauxifen + diclosulan achieving 100% effectiveness, while the 2,4-D combinations were controlled at 80–90%. Aminopyralid caused the highest phytotoxicity (50–75%), while dicamba caused less than 25% phytotoxicity. Aminopyralid also significantly reduced yield and thousand-grain weight to nearly zero, whereas the other treatments maintained yields of approximately 2,500 kg ha−1. These results demonstrate the efficacy of auxinic herbicide combinations for managing Conyza spp., provided that the phytotoxic risks to soybean are carefully managed.
Keywords: control; Fleabane; phytotoxicity; resistance; sequential application